THE LEGAL PROTECTION OF LENDERS IN PEER TO PEER LENDING SYSTEM - Budiharto Budiharto; Sartika Nanda Lestari; Gusto Hartanto (LAW REFORM, 2019)
Financial technology based on Peer to Peer Lending is one of the new breakthroughs in financial services institutions in Indonesia. The peer to peer lending platforms are essentially online markets that match the supply and demand of funds as one of the alternative financing mechanisms for individual or business. But there is still few of regulation regarding peer to peer lending. We address two questions by theoretical legal research by examining secondary data through literature studies. First, the mechanism of credit agreements with a peer to peer lending; second, analyze lender’s legal protection in credit agreements in peer to peer lending. Based on the the research, we found that the mechanism of lending through a peer to peer lending credit agreement is in line with Financial Services Authority (Otoritas Jasa Keuangan - OJK) Regulation No. 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services. Futhermore, the protection of legal lenders peer to peer lending from the aspect of law public has been sufficient but in private law, OJK has not been able to provide maximum protection.